2007
DOI: 10.1007/s10658-007-9181-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of root and foliar applications of soluble silicon on powdery mildew control and growth of wheat plants

Abstract: Foliar and root applications of different silicon (Si)-based formulations were evaluated for their effects in reducing powdery mildew and promoting growth of wheat plants. X-ray microanalyses of treated plants revealed that root applications resulted in consistent deposition of Si in the leaves. In terms of powdery mildew control, root applications at 1.7 mM Si gave consistently the best results, reducing disease severity by as much as 80%, regardless of the product used. Although less effective than root appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
82
0
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(110 citation statements)
references
References 19 publications
11
82
0
12
Order By: Relevance
“…The findings of the present study in conjunction with earlier reports on other pathosystems (Guevel et al, 2007;Rezende et al, 2009) indicated that although both foliar and root application of Si is effective in decreasing the intensity of blast, the root application was more effective compared to the foliar application.…”
Section: Discussionsupporting
confidence: 86%
“…The findings of the present study in conjunction with earlier reports on other pathosystems (Guevel et al, 2007;Rezende et al, 2009) indicated that although both foliar and root application of Si is effective in decreasing the intensity of blast, the root application was more effective compared to the foliar application.…”
Section: Discussionsupporting
confidence: 86%
“…Root applications of 1.7 mM Si reduced the severity of powdery mildew disease (Blumeria graminis f. sp. tritici) on wheat by as much as 80% (Guevel et al, 2007). Guo et al (2007) reported that sodium silicate reduced significantly the severity of post-harvest pink rot of Chinese cantaloupe caused by Trichoth-ecium roseum.…”
Section: Air-and Soil-borne Fungimentioning
confidence: 99%
“…This element is absorbed by the plant in the form of monosilicic acid (H 4 SiO 4 ) along with water (mass flow) and accumulates mainly in the maximum perspiration areas as polymerized silicic acid. It promotes the effective control of plant diseases (Amaral et al, 2008;Guével et al, 2007;Pozza et al, 2009) and has been associated with reduced effects of harmful chemical and physical agents (Zhu et al, 2004, Ma & Yamaji, 2006. The benefits of Si can be observed in the growth and production of many grasses such as rice, oats and maize (Wang et al, 2004, Hossain et al, 2007Zanão Júnior et al, 2009) and in some species that are not grass, such as tomatoes and lettuce (Lana et al 2003;Resende et al, 2005).…”
Section: Introductionmentioning
confidence: 99%